First Report of Coexistence of blaSFO–1 and blaNDM–1 β-Lactamase Genes as Well as Colistin Resistance Gene mcr-9 in a Transferrable Plasmid of a Clinical Isolate of Enterobacter hormaechei - Ai, Wenxiu; Zhou, Ying; Wang, Bingjie; Zhan, Qing; Hu, Longhua; Xu, Yanlei; Guo, Yinjuan; Wang, Liangxing; Yu, Fangyou; Li, Xiaolong (Frontiers in Microbiology, 2021)
Many antimicrobial resistance genes usually located on transferable plasmids are responsible for multiple antimicrobial resistance among multidrug-resistant (MDR) Gram-negative bacteria. The aim of this study is to characterize a carbapenemase-producing E. hormaechei 1575 isolate from the blood sample in a tertiary hospital in Wuhan, Hubei Province, China. Antimicrobial susceptibility test showed that 1575 was a MDR isolate. The whole-genome sequencing (WGS) and comparative genomics were used to deeply analyze the molecular information of the 1575 and explore the location and structure of antibiotic resistance genes. The three key resistance genes（blaSFO-1, blaNDM-1, and mcr-9）were verified by PCR and the amplicons were subsequently sequenced. Moreover, the conjugation assay was also performed to determine the transferability of those resistance genes. Plasmid files were determined by the S1 nuclease-pulsed-field gel electrophoresis (S1-PFGE). WGS revealed that p1575-1 plasmid was a conjugative plasmid which possessed the rare coexistence of blaSFO-1, blaNDM-1, and mcr-9 genes and complete conjugative systems. And p1575-1 belonged to the plasmid incompatibility group IncHI2 and multilocus sequence typing ST102. Meanwhile, pMLST type of p1575-1 was IncHI2-ST1. Conjugation assay proved that the MDR p1575-1 plasmid could be transferred to other recipients. S1-PFGE confirmed the location of plasmid with molecular weight of 342,447bp. All these three resistant genes were flanked by various mobile elements, indicating the blaSFO-1, blaNDM-1, and mcr-9 could not only be transferred by the p1575-1 plasmid but also by these mobile elements. Taken together, we report for the first time that the co-existence of blaSFO-1, blaNDM-1, and mcr-9 on a transferrable plasmid in a MDR clinical isolate E.hormaechei, which indicates the possibility of horizontal transfer of antibiotic resistance genes.